2023
DOI: 10.1002/hrdq.21499
|View full text |Cite
|
Sign up to set email alerts
|

Exploring individuals' workplace spirituality in the context of their work teams: A qualitative multi‐case, multi‐team study

Abstract: Spirituality has been associated with a person's desire to perform meaningful work and to feel connected with the community that is being served through this work. Since most adults spend a large amount of their productive hours at work pursuing meaning and purpose in their jobs, the concept of workplace spirituality (WS) has gained considerable attention. The nature of work has also increasingly shifted to the use of teams of expert talent to solve complex problems, thus calls for further research on team mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 104 publications
0
1
0
Order By: Relevance
“…Moreover, this work directly responds to the call by Wang (2019) who suggested that HRD must cross boundaries and by doing so, builds on the best of multiple fields and opens new eras of social science research. We were inspired by and agreed with Alagaraja and Githens (2016) who articulated that the future of HRD goes beyond traditional boundaries of learning and development and is increasingly pushing into other contexts of life, such as workplace spirituality (e.g., McClurg et al, (2023). Here, we connect that to what it could mean in the Future of Work and what implications that could have for work life integration, work life boundaries, and how contexts of work and health are intertwined.…”
Section: Discussion Of Findingsmentioning
confidence: 80%
“…Moreover, this work directly responds to the call by Wang (2019) who suggested that HRD must cross boundaries and by doing so, builds on the best of multiple fields and opens new eras of social science research. We were inspired by and agreed with Alagaraja and Githens (2016) who articulated that the future of HRD goes beyond traditional boundaries of learning and development and is increasingly pushing into other contexts of life, such as workplace spirituality (e.g., McClurg et al, (2023). Here, we connect that to what it could mean in the Future of Work and what implications that could have for work life integration, work life boundaries, and how contexts of work and health are intertwined.…”
Section: Discussion Of Findingsmentioning
confidence: 80%
“…The nursing students had tried not to confront peers directly and sought harmonious relationships. Other studies also found that teammates endeavored to maintain harmonious relationships with peers, particularly in cultures where collective interests were honored over individual ones [43,44]. As a Chinese society, Macau is influenced by the Chinese individualism and collectivist culture.…”
Section: The Barriers Preventing the Development Of Effective Teamsmentioning
confidence: 98%
“…Working becomes meaningful through a transformative focus (Bhaskar and Mishra, 2019) on organizational spirituality identified with an alignedinternally and externallysocially responsible (Barron and Chou, 2017;Salem et al, 2023) and participative (Dutschke et al, 2019) value driven organizational culture, fostering individual spiritual development and well-being (Pawar, 2016). Given this condition, in addition to work, people develop friendly relationships, enhancing cooperation, creativity and innovation (Fasbender et al, 2023), interacting in a synergistic teamwork environment and communicating in a respectful and responsive way, expressing selfreflection (Hunsaker and Ding, 2022;McClurg et al, 2023), helping them to affirm in favor of life (Prabhu and Modem, 2022) fulfilling a purpose (Nehra, 2023), responding even conventionally to existential concerns.…”
Section: Spirituality In the Workplace As An Antidote To Continual (P...mentioning
confidence: 99%
“…The employee-camel is presented as a patient "machine component", that kneels down before faith, before the "sacred work" as a duty (Ramaswamy et al, 2023), seeking effort to the maximum extent for productivity and operational profitability (Hansen et al, 2022). It humbles itself, disdaining its perception and self-destructs by the excessive load it is taking on [work overload (McClurg et al, 2023)], mocking and belittling itself by "glorifying" its irrational choice of self-sacrifice to suffer willingly for business benefit . The workplace is a "barren" desert in which the "loaded camel"-employee sickens under the pressure of job stress physically and mentally (Gregory and Moates, 2023), conversely affecting its change readiness (Bhattacharya et al, 2021), but does not want to be healed or comforted [work addiction (McClurg et al, 2023)].…”
Section: Camel: the First Metamorphosis Of The Spiritmentioning
confidence: 99%
See 1 more Smart Citation